Internet usage behaviors among young teenagers - Amran, Noraizan; Saiful Bahry, Farrah Diana; Anwar, Norizan; Abu Bakar, Rosiah (Faculty of Information Management, 2013)
This study identifies the Malaysian suburban young teenagers' behavior on internet usage: types of information, online activities, and internet topic of interest. This study also investigates the relationship between gender and internet usage behavior. A set of 350 questionnaires have been distributed to a group of young teenagers' age 11-12 years old in Year Six of primary schools in suburbs of Selangor. A total of 297 completed responses have been received and analyzed using Microsoft Excel and SPSS. The findings indicate that although young teenagers at suburban prefer to search entertainment information, do leisure activities and are interested in non-serious topic, most of the time, they still search information, do online activities and interested on educational information at other time. Further research can be conducted on information content preferences of young teenagers in other parts of Malaysia.